2020
DOI: 10.1007/s00134-020-06198-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of poor neurological outcome in comatose survivors of cardiac arrest: a systematic review

Abstract: Purpose: To assess the ability of clinical examination, blood biomarkers, electrophysiology, or neuroimaging assessed within 7 days from return of spontaneous circulation (ROSC) to predict poor neurological outcome, defined as death, vegetative state, or severe disability (CPC 3-5) at hospital discharge/1 month or later, in comatose adult survivors from cardiac arrest (CA). Methods: PubMed, EMBASE, Web of Science, and the Cochrane Database of Systematic Reviews (January 2013-April 2020) were searched. Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
268
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(290 citation statements)
references
References 180 publications
(592 reference statements)
5
268
4
13
Order By: Relevance
“…The presence of status myoclonus may be more specific ( 2 ), but the associated electrophysiology is critical, as patients with persistent myoclonus but distinct EEG patterns have achieved a good outcome ( 17 , 18 ). In contrast, pupillary and corneal reflexes boast strong evidence in support of their utility, as their false-positive rates are reportedly low though nonzero at 72-hour postarrest or postrewarming ( 2 , 3 , 19 ). In our cohort, pupillary reflexes were most commonly assessed using light with the naked eye; however, studies have demonstrated greater specificity and interrater reliability through use of automated pupillometry ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of status myoclonus may be more specific ( 2 ), but the associated electrophysiology is critical, as patients with persistent myoclonus but distinct EEG patterns have achieved a good outcome ( 17 , 18 ). In contrast, pupillary and corneal reflexes boast strong evidence in support of their utility, as their false-positive rates are reportedly low though nonzero at 72-hour postarrest or postrewarming ( 2 , 3 , 19 ). In our cohort, pupillary reflexes were most commonly assessed using light with the naked eye; however, studies have demonstrated greater specificity and interrater reliability through use of automated pupillometry ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SSEP and NSE testings were less accessible and less frequently used. SSEP was still considered highly important, mirroring its high reliability in the literature ( 14 , 15 , 19 ); however, the majority reported never using this modality, likely due to its unavailability. NSE testing was regarded as less important—perhaps a reflection of its unavailability as well as its more tenuous evidence base, particularly as optimal cutoff levels remain controversial and are assay-dependent ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most severe complication of sudden cardiac death is hypoxic-ischemic brain injury (HIBI) [ 1 ]; most patients admitted to an intensive care unit (ICU) after resuscitation from either out-of-hospital (OHCA) or in-hospital cardiac arrest (IHCA) are comatose and about two-thirds of them will eventually die before hospital discharge because of irreversible brain damage [ 2 ]. Moreover, severe cognitive dysfunction can affect up to 20% of cardiac arrest survivors with favorable neurological recovery [ 3 ] and potential neuroprotective therapies remains one of the most relevant strategies in this setting [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it helps to provide correct information for patients’ relatives, and, in case of a scarcity of resources, to allocate resources appropriately. A recent study showed that in case of resuscitation from out-of-hospital cardiac arrest more than 80% of patients admitted to an ICU have hypoxic–ischemic brain injury and about two-thirds of them die from withdrawal of life-sustaining treatment due to a predicted poor neurological outcome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%